Child implant users' imitation of happy- and sad-sounding speech - Wang, David J.; Trehub, Sandra E.; Volkova, Anna; van Lieshout, Pascal (Frontiers in Psychology, 2013)
Cochlear implants have enabled many congenitally or prelingually deaf children to acquire their native language and communicate successfully on the basis of electrical rather than acoustic input. Nevertheless, degraded spectral input provided by the device reduces the ability to perceive emotion in speech. We compared the vocal imitations of 5- to 7-year-old deaf children who were highly successful bilateral implant users with those of a control sample of children who had normal hearing. First, the children imitated several happy and sad sentences produced by a child model. When adults in Experiment 1 rated the similarity of imitated to model utterances, ratings were significantly higher for the hearing children. Both hearing and deaf children produced poorer imitations of happy than sad utterances because of difficulty matching the greater pitch modulation of the happy versions. When adults in Experiment 2 rated electronically filtered versions of the utterances, which obscured the verbal content, ratings of happy and sad utterances were significantly differentiated for deaf as well as hearing children. The ratings of deaf children, however, were significantly less differentiated. Although deaf children’s utterances exhibited culturally typical pitch modulation, their pitch modulation was reduced relative to that of hearing children. One practical implication is that therapeutic interventions for deaf children could expand their focus on suprasegmental aspects of speech perception and production, especially intonation patterns.